Timing of Maternal Discharge after Cesarean Delivery and Risk of Maternal Readmission - Oben, Ayamo; Perez, William; Jauk, Victoria C.; Boggess, Kim; Clark, Erin; Saade, George; Esplin, M Sean; Longo, Sherri; Cleary, Kirsten L.; Wapner, Ronald; Blackwell, Sean C.; Owens, Michelle Y.; Ambalavanan, Namasivayam; Szychowski, Jeff M.; Tita, Alan (American Journal of Perinatology, 2022)
Objective Despite legislation and hospital policies (present in some institutions) mandating a minimum length of stay in an effort to decrease the frequency of hospital readmissions, the effectiveness of this approach remains uncertain.We hypothesized that following cesarean delivery (CD), the rates of maternal readmission or unscheduled health care visits are lower in patients discharged on postoperative day (POD) 3 or ≥4 as compared with those discharged earlier on POD 2.Methods This is a secondary analysis of a multicenter randomized trial comparing adjunctive azithromycin for unscheduled CD to prevent infection. Groups were compared based on the duration of hospitalization measured in days from delivery (POD 0) to day of discharge and categorized as POD 2, 3, and ≥4. The primary outcome was the composite of any maternal postpartum readmission, unscheduled clinic, or emergency room (ER) visit, within 6 weeks of delivery. Secondary outcomes included components of the primary outcome and neonatal readmissions. We excluded women with hypertensive disorders of pregnancy and infections diagnosed prior to POD 2.Results A total of 1,391 patients were included. The rate of the primary outcome of any readmission increased with POD at discharge: 5.9% for POD 2, 9.4% for POD 3, and 10.9% for POD ≥4 group (trend for p = 0.03). The primary outcome increased with later discharge (POD ≥4 when compared with POD 2). Among components of the composite, ER and unscheduled clinic visits, but not maternal readmissions, increased with the timing of discharge for patients discharged on POD ≥4 when compared with POD 2. Using logistic regression, discharge on POD 3 and on POD ≥4 was significantly associated with the composite (adjusted odds ratios [aOR] 2.6, 95% confidence interval [CI] [1.3–5.3]; aOR 2.9, 95% CI [1.3–6.4], respectively) compared with POD 2.Conclusion The risk of maternal readmission composite following uncomplicated but unscheduled CD was not lower in patients discharged home on POD 3 or ≥4 compared with patients discharged earlier (POD 2).Key Points
Keywords: hospital discharge; unscheduled cesarean delivery; maternal readmissions; neonatal readmissions